1981
DOI: 10.1111/j.1095-8649.1981.tb03780.x
|View full text |Cite
|
Sign up to set email alerts
|

The influences of feeding on the metabolic rate of fishes: a short review

Abstract: Following feeding, the rate of oxygen consumption of fishes increases to a peak and then slowly declines to the pre-feeding level. Many factors have been shown to influence the magnitude and duration of post-prandial oxygen consumption and these include quantity and/or quality of ration and environmental temperature. The effects of the various factors are described and the phenomenon of the post-prandial increase in metabolic rate of fish is discussed in relation to work with other species of animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
244
1
3

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(264 citation statements)
references
References 59 publications
16
244
1
3
Order By: Relevance
“…The near doubling of the O 2 consumption during the SDA at 24 h fits well with the normal results in most water-breathing animals (21,22,25). This study showed that postprandial O 2 consumption was abruptly reduced by exposing animals to water at a PO 2 of 3 kPa (arterial PO 2 ϭ 0.5-0.6 kPa) but not to water PO 2 of 4 kPa (arterial PO 2 of 0.6-0.8 kPa).…”
Section: Discussionsupporting
confidence: 70%
“…The near doubling of the O 2 consumption during the SDA at 24 h fits well with the normal results in most water-breathing animals (21,22,25). This study showed that postprandial O 2 consumption was abruptly reduced by exposing animals to water at a PO 2 of 3 kPa (arterial PO 2 ϭ 0.5-0.6 kPa) but not to water PO 2 of 4 kPa (arterial PO 2 of 0.6-0.8 kPa).…”
Section: Discussionsupporting
confidence: 70%
“…4). In general, feeding increases the oxygen consumption in organisms; which is associated with numerous mechanical and biochemical processes related with food ingestion, digestion absorption and assimilation as well as, protein synthesis and deposition (Fu et al, 2006;Jobling, 1981). Jobling (1994) suggested that the maximum rate of oxygen consumption induced by feeding appears to be approximately double of fasted metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that, at least in discontinuous feeders, growth tends to occur in a pulse immediately following a meal. The respiratory cost of growth may thus explain much of the post-prandial increase in oxygen consumption (the specific dynamic action, SDA : Jobling 1981: Jobling ,1983, and perhaps nitrogen excretion (Bayne & Scullard 1977). In the starfish Asterias rubens, for example, there is a strong correlation between the extent of SDA and overall growth rate (Vahl 1984).…”
Section: Seasonality and The Energy Budgetmentioning
confidence: 99%